Degree of arterial stiffness is comparable across inflammatory joint disease entities. (4th May 2022) - Föhse, FK; Rollefstad, S; Ikdahl, E; Wibetoe, G; Sexton, J; Hisdal, J; Semb, AG
Abstract : Objectives: Inflammatory joint disease (IJD) is associated with an increased risk of developing cardiovascular disease (CVD). Arterial stiffness is both a risk factor and a surrogate marker for CVD. This study aims to compare arterial stiffness across patients with rheumatoid arthritis, ankylosing spondylitis, and psoriatic arthritis, and, by extension, to explore the relationship between arterial stiffness and the estimated CVD risk by the Systematic COronary Risk Evaluation (SCORE) algorithm. Method: During the study period, from April 2017 to June 2018, 196 patients with IJD visited the Preventive Cardio-Rheuma Clinic in Oslo, Norway. A CVD risk stratification was performed, including the assessment of traditional risk factors and the measurement of arterial stiffness. Results: Thirty-six patients (18.4%) had elevated aortic pulse wave velocity (aPWV) (≥ 10 m/s). After adjustment for age and heart rate, arterial stiffness was comparable across the IJD entities (p = 0.69). Associated factors, revealed by regression analysis, were age, blood pressure, heart rate, presence of carotid plaques, establis hed CVD, non-steroidal anti-inflammatory drugs, and statin use. Furthermore, aPWV was positively correlated with estimated CVD risk (r = 0.7, p < 0.001) and patients with a very high predicted CVD risk (SCORE ≥ 10%) had significantly higher aPWV than patients at lower CVD risk (9.2 vs 7.5 m/s, p < 0.001). Conclusion: The degree of arterial stiffness was comparable across the IJD entities and was highly associated with the estimated CVD risk. Our findings support the need for an increased focus on prevention of CVD in all patients with IJD.